The sepiapterin reductase gene region reveals association in the PARK3 locus: analysis of familial and sporadic Parkinson's disease in European populations. Issue 7 (27th January 2006) - Sharma, M; Mueller, J C; Zimprich, A; Lichtner, P; Hofer, A; Leitner, P; Maass, S; Berg, D; Dürr, A; Bonifati, V; De Michele, G; Oostra, B; et al.
Abstract : Background: Parkinson's disease is a genetically complex disease with mixed mode of inheritance. Recently, a haplotype across the sepiapterin reductase (SPR) gene, which is located in the PARK3 linkage region, was shown to modulate age of onset of Parkinson's disease in sibships from North America. Objective: To make a thorough assessment of the SPR gene region in sporadic Parkinson's disease. Methods: A linkage study in 122 European sibship families with five microsatellite and 17 single nucleotide polymorphism (SNP) markers in and around the SPR gene region, and an association analysis in 340 sporadic cases of Parkinson's disease and 680 control subjects from Germany with 40 SNPs. Linkage was evaluated by non-parametric linkage scores and genotypic or haplotype association was tested by regression analysis, assuming different risk effect models. Results: Significant LOD scores between 2 and 3 were obtained at the two SPR-flanking markers D2S2110 and D2S1394 and seven SNP markers around the SPR gene. We found the previously reported promoter SNP rs1876487 also significantly associated with age of onset in our sib pair families (p-value 0.02). One strong linkage disequilibrium (LD) block of 45 kb including the entire SPR gene was observed. Within this LD block all 14 inter-correlated SNPs were significantly associated with Parkinson's disease affection status (p-value 0.004). Conclusions: DNA polymorphisms in a highly intercorrelated LD block, which includes the SPR gene, appear to be associated with both sporadic and familial Parkinson's disease. This confirms a previous study showing that SPR potentially modulates the onset of or risk for Parkinson's disease.